Nutritional status and risk of Lupus Nephritis among SLE patients a case-control study - Flandes, Jose Raphael M.; Jacinto, Beatrice Marie V.; Santos, Alysa Aileen L.; Cabigas, Cecile Klaudine C. (Quezon City College of Home Economics, University of the Philippines Diliman, 2023)
Systemic Lupus Erythematosus (SLE) is an autoimmune disease causing widespread inflammation and tissue damage (CDC, 2018). There is an approximately 0.03 to 0.05% chance that an Asian is affected, commonly women of child-bearing age (Zamora, 2019). Its nutrition therapy currently includes hypocaloric diets and protein restriction to prevent progression into conditions such as Lupus Nephritis (LN). However, its dietary management needs further investigation due its lack of a well established diet (Constantin et al., 2018). This study aimed to investigate the relative risk (RR) of nutritional status with LN development in SLE patients. Specifically, it looked into anthropometric data (BMI & WHR), SGA score, and intake of protein, sodium, oleic acid, polyunsaturated fatty acids (PUFA), fiber, vitamins D, E, and C. Thirty (30) patients were eligible for the criteria, and were divided into case (SLE-LN) and control (SLE only) groups. Data were statistically analyzed to establish significant values for RR of these nutritional aspects. Above-normal WHR was associated with an increased risk of developing LN (p = 0.03). Protein and sodium consumption were significantly excessive in patients without LN, possibly due to the gap in awareness of its reduction between cases and controls. Inadequate Oleic Acid and Vitamin D intake only produced significant RR (1.25 & 2), excluding significant differences in means. Both groups exhibited excessive Vitamin C intake. The findings were only conclusive for LN risk associated with WHR. As for other aspects, despite lacking significance, the trends in data may help future researchers determine the possibilities of exploring such and create more specific methodologies to address the gaps in this research.
Thesis (Bachelor of Science in Community Nutrition) -- University of the Philippines Diliman
Bibliography: pages 89-105.
Keywords: Systemic lupus erythematosus -- Philippines -- Nutritional aspects; Lupus nephritis -- Philippines -- Nutritional aspects; Systemic lupus erythematosus -- Patients -- Philippines